Analysis of Financial Distress Potential Using the Zmijewski Method in Coal Mining Subsector Companies Listed on the Indonesia Stock Exchange for the 2019-2023 Period - Rosyada, Amalia Amrina Rosyada; Maria Theresia Heni Widyarti; Musyafa Alfarizi (Applied Accounting and Management Review (AAMAR), 2025)
Significant fluctuations in coal prices during the 2019-2023 period impacted the financial performance of coal mining subsector companies listed on the Indonesia Stock Exchange. This condition increased the risk of financial distress, which refers to financial difficulties that could potentially lead to bankruptcy if not properly addressed. This research aims to analyze, determine the accuracy level, and formulate strategies to address potential financial distress in 14 selected companies using the purposive sampling method. This descriptive quantitative research utilizes financial report data from 2019-2023, analyzed using the Zmijewski method, which involves the Return on Assets (ROA), Debt Ratio, and Current Ratio. The results indicate that, on average, companies remained in the non-financial distress category throughout the period. However, two companies, CNKO and DWGL, consistently experienced financial distress. Additionally, AIMS faced financial distress in 2023, BSML in 2019, and CBRE from 2019 to 2021. The accuracy rate of the Zmijewski X-Score method was 77%, with an error rate of 23%. Strategies for addressing financial distress include increasing ROA through operational efficiency, prudent debt management to reduce the Debt Ratio, and managing current liabilities, inventory, and receivables to improve the Current Ratio.